PENGARUH REALISASI HUTANG PAJAK, REALIASI SKPKB, DAN JUMLAH WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN - Aulia Azzahra; Widi Dwi Ernawati; Ludfi Djajanto (Politeknik Negeri Malang, 2023)
The aims of this study are to examine, both partially and simultaneously, the effects on realization of tax debt, realization of SKPKB, and the number of taxpayers on income tax revenues at the Pratama Tax Office in Southern Malang. This is quantitative research with causal associative research. The instruments of the data collection are documention and interview. The data used in this research are monthly realization reports, which amount to 60 samples (starting from January 2016 to December 2020) of income tax revenue paragraph 25/29, tax debt settled, (SKPKB) Notice of Tax Underpayment Assessment, and the number of registered individual and corporate taxpayers. The data are analyzed with classic assumption, and Multiple Linier Regression analysis of SPSS version 25. The analysis shows realization of tax debt, realization of SKPKB, and the number of taxpayers have a significant value of 0.013. It means that there is a simultaneous effect on income tax revenues. This research also found that realization of tax debt has a significant value of 0.045 and the number of taxpayers has a significant value of 0.012. It means that there is a partial effect on income tax revenues. However partially, realization of SKPKB does not have a significant effect on income tax revenues. This is evidenced by the significance value of t > α which is 0,117 > 0,05. Thus, when the realization of SKPKB is high or low, it will not have an effect on the income tax revenues.